Risk of emergency hospital admission in children associated with mental disorders and alcohol misuse in the household: an electronic birth cohort study. (June 2018) - Paranjothy, Shantini; Evans, Annette; Bandyopadhyay, Amrita; Fone, David; Schofield, Behnaz; John, Ann; Bellis, Mark A; Lyons, Ronan A; Farewell, Daniel; Long, Sara Jayne
Summary: Background: Mental disorders and alcohol misuse are common in families but their effects on the physical health of children are not known. We investigated the risk of emergency hospital admissions during childhood associated with living with an adult who has a mental health disorder, or who had an alcohol-related hospital admission. Methods: We did this cohort study in a total population electronic child cohort in Wales, UK, which includes all children who live in Wales or with a mother who is resident in Wales. We used Cox regression to model time to first emergency hospital admission during the first 14 years of life associated with living with an adult who has a mental health disorder, or who had an alcohol-related hospital admission. We adjusted our results for social deprivation and perinatal risk factors. Findings: We included data for 253 717 children with 1 015 614 child-years of follow-up. Living with an adult with a mental disorder was associated with an increased risk of emergency admission for all causes (adjusted hazard ratio [aHR] 1·17, 95% CI 1·16–1·19), for injuries and external causes (1·14, 1·11–1·18), and childhood victimisation (1·55, 1·44–1·67). Children living with a household member who had an alcohol-related hospital admission had a significantly higher risk of emergency admissions for injuries and external causes (aHR 1·13, 95% CI 1·01–1 ·26) and victimisation (1·39, 1·00–1·94), but not for all-cause emergency admissions (1·01, 0·93–1·09). Interpretation: The increased risk of emergency admissions in children associated with mental disorders and alcohol misuse in the household supports the need for policy measures to provide support to families that are affected. Funding: Economic and Social Research Council, Medical Research Council, Alcohol Research UK, Public Health Wales.